2020
DOI: 10.12688/f1000research.26215.1
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity in secondary metabolite extracts of heterotrophic bacteria against Vibrio alginolyticus, Aeromonas hydrophila, and Pseudomonas aeruginosa

Abstract: Background: Disease causing bacteria such as Vibrio alginolyticus, Aeromonas hydrophila, and Pseudomonas aeruginosa present a problem for fish farming. Treatment to remove them are generally carried out using antibiotics which have side effects on fish, the environment and humans. However, the use of antibacterial compounds derived from heterotrophic bacteria serve as a good alternative for antibiotics. Therefore, this study aimed to explore antibacterial activity in the secondary metabolite extracts of hetero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…To explain antimicrobial spectra, all of the 16 Vi+ were checked for antimicrobial biosynthetic gene clusters relating to the production of non-ribosomal peptides, polyketide type I (PKS-I), and polyketide type II (PKS-II). These antimicrobial substances have shown activity against a wide range of other bacteria including Vibrio species [ 6 , 13 , 14 ]. A PCR reaction was performed to amplify conserved gene regions within the genes coding non-ribosomal peptide synthetase (NRPS), polyketide type I synthetase (PKS-I), and polyketide synthetase (PKS-II) enzymes.…”
Section: Methodsmentioning
confidence: 99%
“…To explain antimicrobial spectra, all of the 16 Vi+ were checked for antimicrobial biosynthetic gene clusters relating to the production of non-ribosomal peptides, polyketide type I (PKS-I), and polyketide type II (PKS-II). These antimicrobial substances have shown activity against a wide range of other bacteria including Vibrio species [ 6 , 13 , 14 ]. A PCR reaction was performed to amplify conserved gene regions within the genes coding non-ribosomal peptide synthetase (NRPS), polyketide type I synthetase (PKS-I), and polyketide synthetase (PKS-II) enzymes.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, Lopes et al [ 49 ] sequenced the whole B. toyonensis BAC3151 genome and found that it had a higher frequency of putative bacteriocin gene clusters than that of Bacillus species used traditionally for production of antimicrobials. In turn, secondary metabolite extracts produced by B. toyonensis collected from sea waters inhibited the growth of Vibrio alginolyticus , Aeromonas hydrophila , and Pseudomonas aeruginosa [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Possibly one or several combinations of these mechanisms was responsible for these results. Several studies showed that B. cereus is capable of inhibiting V. alginolyticus (Feliatra et al 2021;Setiaji et al 2020), by producing secondary metabolites compounds i.e., alkaloid, flavonoid, and saponin (Feliatra et al 2021). These secondary metabolites compounds are capable to disrupt the peptidoglycan, one of the major constituents of bacterial cell wall, that causes lysis in cells (Feliatra et al 2021).…”
Section: Antibacterial Activitymentioning
confidence: 99%